Cultivo do camarão-da-amazônia, Macrobrachium amazonicum (Heller, 1862) (Crustacea, Decapoda, Palaemonidae) em diferentes densidades: fatores ambientais, biologia populacional e sustentabilidade econômica - Moraes-Riodades, Patrícia Maria Contente [UNESP] (2005)
The aim of this research was to study Macrobrachium amazonicum farming in grow-out ponds at different levels of intensification. Post-larvae (0.01g) were stocked in 12 earthen ponds at densities of 10, 20, 40 and 80/m2 (3 replicates per treatment) during 5.5 months. Commercial marine shrimp diet (40% protein) was supplied for twelve days and, then, prawns were fed a pelleted diet, containing 37% protein, twice daily. At harvest, it was observed large size heterogeneity because population structure is comprised of four different male morphotypes and females at different maturation stages. GC1 and GC2 males and all females weight increased along time while TC and CC males did not grow. Average individual weight decreased and production increased as stocking density increased, while survival was not affected. Therefore, prawn density plays an important role on M. amazonicum growth and population structure, as have been demonstrated for other species of the genus Macrobrachium. It may be due to biological characteristics of the species and/or competition for space and natural food. On the other hand, intensification did not affected water quality. A hypothetical commercial pond farm was developed to assess economic sustainability of the amazon river prawn farming. It was based upon technology, harvest population structure and productivity data obtained in the experiment carried out here. Three different analyses for investment evaluation were performed: cost-return analysis, cash flow analysis and financial investment analysis. Breakeven cost decreased from US$ 6,50 to 4,80 by kg as density increased. General results indicated that the species might be raised in intensive systems. Despite of the small size (mean weight 7 g), high survival (about 70%) and productivity (more than 4,000 tonnes/ha/yr) may be attained using high stocking densities. The use of management practices to decrease heterogeneous ...